Elective surgery: operational forecast and decision-making - N. A. Kuznetsov (Сеченовский вестник)
The article is devoted to operational forecasting and decision-making features in elective surgery. The paper presents the original formula predictive of death based on the study of operational outcomes described five types of predictions. It is shown that only a combination of normative and descriptive hiking allows you to build evidence based decision making. Only the application of the scientific approach will allow the person making the decision, more objectively assess a problem situation, to take into account the available resources and constraints to formulate and analyze solutions, choose from them acceptable. In the article the problem of operational forecasting and rational theory of decision making in general and oncology considered and developed as an integrated, interdisciplinary, involving philosophy, mathematics, statistics and psychology.